Economics of large-scale intermittent RES-E integration into the European grids: analyses based on the simulation software GreenNet. (13th February 2006) - Auer, Hans; Huber, Claus; Faber, Thomas; Resch, Gustav; Obersteiner, Carlo; Weissensteiner, Lukas; Haas, Reinhard
Market integration of Renewable Energy Technologies for Electricity (RES-E) generation is one of the core topics in the energy policy agenda of the European Commission (EC). However, legislation in this context still faces a variety of lacks (e.g. ignoring unbundling principles) in almost all countries of the European Union (EU). The recently finished EC-Project GreenNet addresses these existing inadequacies and models dynamic time paths up to the year 2020 for a variety of least-cost RES-E grid integration cases in the EU for different degrees of unbundling and different cost allocation schemes. The major results derived from GreenNet clearly demonstrate that the degree of unbundling and the implemented allocation principles of different disaggregated cost elements significantly influence RES-E deployment both on national as well as on EU level up to the year 2020. The major conclusion is that serious unbundling and correct allocation of RES-E related grid integration costs only guarantee the fulfilment of the ambitious EC goals with minimal costs for society.